When large marine predators feed on fisheries catches: Global patterns of the depredation conflict and directions for coexistence - Tixier, Paul; Lea, Mary‐Anne; Hindell, Mark A.; Welsford, Dirk; Mazé, Camille; Gourguet, Sophie; Arnould, John P. Y. (Fish and fisheries (Oxford, England), 2021)
The sustainable mitigation of human–wildlife conflicts has become a major societal and environmental challenge globally. Among these conflicts, large marine predators feeding on fisheries catches, a behaviour termed “depredation,” has emerged concomitantly with the expansion of the world’s fisheries. Depredation poses threats to both the socio‐economic viability of fisheries and species conservation, stressing the need for mitigation. This review synthesizes the extent and socio‐ecological impacts of depredation by sharks and marine mammals across the world, and the various approaches used to minimize it. Depredation was reported in 214 fisheries between 1979 and 2019 (70% post‐2000) and affected fleets from 44 countries, in all sectors (commercial, artisanal and recreational), and in all major fishing techniques (nets, traps and hook‐and‐lines). A total of 68 predator species were involved in depredation (20 odontocetes, 21 pinnipeds and 27 sharks), and most (73%) were subject to either by‐catch and/or retaliatory killing from fishers when interacting with gear. Impacts on fishers were primarily associated with catch losses and gear damage but often lacked assessments. Deterrence was a major mitigation approach but also the least effective. Gear modifications or behavioural adaptation by fishers were more promising. This review highlights the need for improved monitoring, and interdisciplinary and integrated research to quantify the determinants and impacts of depredation in the socio‐ecological dimension. More importantly, as the conflict is likely to escalate, efforts directed towards changing perceptions and integrating knowledge through adaptive co‐management are raised as key directions towards coexistence between fisheries and large marine predators.